One-step biotransformation of ferulic acid into biovanillin using recombinant Escherichia coli BL21 (DE3) - Zamzuri, Nur Ain (2016)
Vanillin is one of the most important flavour compounds used in foods, beverages,perfumes and pharmaceuticals industry through isolation from vanilla pods of Vanilla planifolia or chemical synthesis. An alternative biotechnology-based approach for biovanillin production is searched for due to the high price of natural vanillin that isolated from vanilla pods and rising on demand for naturally produced foods. Vanillin production through biotechnology routes is focused on the microbial bioconversion from precursors like ferulic acid and eugenol. However, the common problem regarding biovanillin production is the oxidation pathway of vanillin into vanillic acid.Thus, low vanillin is detected as the desired product. The objective of this study includes the construction of recombinant Escherichia coli that can be further utilized for biotransformation of ferulic acid into biovanillin by one step fermentation withoutfurther oxidation of vanillin into vanillic acid. The desired genes involving in biovanillin production, enoyl-CoA hydratase (ech) andferuloyl-CoA synthetase (fcs)are screened and isolated from locally isolated bacteria, later named as Pseudomonassp. AZ10 UPM. It showed the highest degradation of ferulic acid as carbon source with the yield, Yp/s and productivity, Pr obtained were 1.08 mg/mg and 53.1 mg/L/h,respectively. Oxidation of vanillin into vanillic acid was observed lead to low vanillin production after 48 hours of incubation. Therefore, this strain was selected as the potential vanillin producer due to accumulation of vanillic acid at the end of ermentation process with assumption that vanillin was oxidized into vanillic acid.Further study was conducted on the isolation of biovanillin producing gene from Pseudomonas sp. AZ10 UPM. By using DNA walking strategy, full length of both enoyl co-A hydratase (ech) and feruloyl co-A synthetase (fcs) were successfully isolated. Analysis of the nucleotide sequences revealed the presence of an open reading frame of 906 bp with protein encoded 302 amino acids and 1869 bp with protein encoded 623 amino acids of ech and fcs,respectively. The deduced amino acids for ech and fcs about 62% and 98% homology with Pseudomonas sp., respectively. The recognition of GTG (Guanine-Thymine-Guanine) for both genes ech and fcs as start codon was assisted by the presence of Shine-Dalgarno sequence, which located at 8 bp for ech and 7 bp for fcs upstream the initiation codon. The pRSFDuet-1/ech-fcs ii expression system has been constructed by cloning the full length of fcs and ech under the transcriptional control of T7 promoter of pRSFDuet-1 into an E. coli BL21 (DE3).In comparison to wild type, Pseudomonas sp. AZ10 UPM, this recombinant E. coli harbouring pRSFDuet-1/ech-fcs was able to produce vanillin in one step fermentation without further oxidation of vanillin into vanillic acid. In order to confirm the genes expression for vanillin production, fermentation was done in 2YT medium with supplementation of 0.1% (w/v) ferulic acid. From the observation, the recombinant Escherichia coli able to produce 165 mg/L vanillin by one step fermentation without further oxidation into vanillic acid. Furthermore, the recombinant shows the ability to convert agricultural waste containing ferulic acid into vanillin. It was able to convert 200 mg/L oil palm empty fruit bunches (OPEFB) alkaline hydrolysate into 27 mg/L vanillin with no vanillic acid detected as the oxidized product. In conclusion, this study was successfully developed a recombinant Escherichia coli BL21 (DE3) with plasmid harbouring key genes for biovanillin production which were ech and fcs. The recombinant was able to produce biovanillin in one step fermentation without further oxidation of vanillin into vanillic acid. In fact, it shows potential to utilize agricultural waste, OPEFB alkaline hyrdrolysate as natural source of ferulic acid for biovanillin production.